The World Heart Federation criteria raise the threshold of diagnosis for mild rheumatic heart disease: Three reviewers are better than one. (15th September 2019) - Culliford-Semmens, Nicola; Nicholson, Ross; Tilton, Elizabeth; Stirling, John; Sidhu, Karishma; Webb, Rachel; Wilson, Nigel
Abstract: Background: The World Heart Federation (WHF) criteria, published in 2012, provided an evidence-based guideline for the minimal diagnosis of echocardiographically-detected RHD. Primary aim of the study was to determine whether use of the WHF criteria altered the threshold for the diagnosis of echocardiographically-detected RHD compared with the previous WHO/NIH criteria. A secondary aim was to explore the utility of a three reviewer reporting system compared to a single or two reviewer reporting structure. Methods: 144 de-identified echocardiograms (RHD, congenital valvar abnormality, physiological valvar regurgitation) were independently reported using the WHF criteria by two reviewers blinded to the previous WHO/NIH diagnosis. If there was discordance between the two reviewers, a third cardiologist independently performed a tie-breaker review. Results: There was a 21% reduction of cases classified as RHD using the WHF criteria compared to the modified WHO/NIH criteria (68 cases compared to 86, p = 0.04). There was a 60% consensus across the different diagnostic categories with 2 reviewers, 89% majority agreement with 3 reviewers. 11% required an open label discussion. There was moderate agreement between 2 reviewers for any RHD, kappa 0.57 (CI 0.44–0.70), with no significant difference in agreement between the different categories. Conclusion: The WHF criteria have raised the threshold for the diagnosis of RHD compared to the WHO/NIH criteria. However, inter-reporter variability of the WHF criteria is high. A three reviewer system is likely more accurate than a single or two reporter system for the diagnosis of mild RHD. This has resource implications for echocardiographic screening programmes. Highlights: The WHF criteria raise the threshold of diagnosis of echocardiographically-detected RHD compared to WHO/NIH criteria. This study reveals that there is only moderate rather than high inter-observer agreement of mild RHD changes. The study recommends a panel of 3 reviewers for evaluation of abnormal cases detected by RHD screening programs, but this has significant resource implications for many regions.